Pengujian Organoleptik Nugget Fortifikasi Tepung Daun Kalakai Pretreatment Asam Jeruk Nipis - Ayutha Wijinindyah; Salsa Arifa Putri; Andrey Rolis Saputra (JURNAL AGROINDUSTRI HALAL, 2025)
Kalakai (Stenochlaena palustris) is a typical Kalimantan fern that grows wild in peat soils. It contains high levels of nutrients, particularly iron (4.153 mg/100 g), which can be beneficial for treating anemia. However, its utilization remains very limited, thus innovation is needed to develop it into nutritious food products, including fortification into chicken nugget production. Kalakai leaf flour was prepared by drying at 50°C until the moisture content reached below 10%, preceded by soaking in 0.5% lime solution (acid pretreatment) to accelerate drying, minimize color loss, and preserve nutrient content. The flour was then added to the nugget mixture at concentrations of 5%, 10%, and 15%, compared to a control group. This study employed a Completely Randomized Design (CRD) with four treatments and three replications. Organoleptic tests were analyzed using SPSS ANOVA. The results showed that each treatment differed significantly (p ≤ 0.05). The addition of 5% kalakai leaf flour achieved the highest acceptance by the panelists. It is hoped that the results of this study will encourage public interest in processing kalakai to enhance the nutritional value of food products.